2004
DOI: 10.1180/0009855043940148
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of swelling in unsaturated compacted clays

Abstract: International audienceThis paper describes the swelling properties of two highly compacted clays, natural, untreated Wyoming montmorillonite (MX80) and Fourges smectite (FoCa7), saturated with Na and Ca, respectively.The initially compacted samples were hydrated by subjecting them to different suction pressures in a range between 100 MPa and 1 kPa. For each equilibrium state, the volume change (swelling) and water content (hydration) were measured. The samples were then studied by X-ray diffraction using a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(99 citation statements)
references
References 20 publications
4
79
0
Order By: Relevance
“…These swelling mechanisms may cause a significant breakdown of the clay particles made up of several hundreds of stacked unit layers when the adsorbed interlayer water is more than two [11][12]. The complete separation of two swelling phenomena appears to be difficult since they can coexist as shown by Saiyouri et al [11][12][13]. The predominance of the one over the other highly depends on the hydration conditions.…”
Section: Discussion On Multiscale Coupling Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…These swelling mechanisms may cause a significant breakdown of the clay particles made up of several hundreds of stacked unit layers when the adsorbed interlayer water is more than two [11][12]. The complete separation of two swelling phenomena appears to be difficult since they can coexist as shown by Saiyouri et al [11][12][13]. The predominance of the one over the other highly depends on the hydration conditions.…”
Section: Discussion On Multiscale Coupling Behaviourmentioning
confidence: 99%
“…As shown by the previous studies [9][10][11][12][13], the occurrence of swelling of expansive minerals consists of the development of crystalline swelling and osmotic swelling, which is associated with the hydration of inter-layer and interparticle pore spaces, respectively. In case of Na dominated bentonites, the crystalline swelling may widen the basal spacing, accommodating up to 4 layers of water molecules, while the osmotic swelling is mainly related to the formation of electrical diffuse double-layers [10][11][12].…”
Section: Discussion On Multiscale Coupling Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Mooney et al,9). Typically, the first layer is observed at high suctions of various hundreds of MPa, whereas the second one is observed under various tens of MPa and the third one below around 9 MPa (see also Saiyouri et al,10). XRay diffraction investigations also showed that, starting from a inter-basal spacing of 9.6 Å for illite and smectite, inter-basal spacings of 12,5, 15,5 and 18,5 Å corresponded to the hydrated states of smectite with 1, 2 and 3 layers of water molecules, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Theˆgure shows that MX80 is the most active material as compared to the other bentonites. In addition, Saiyouri et al (2004) reported the diŠerence of hydration mechanism between sodium bentonite (i.e., MX80) and calcium bentonite (i.e., FoCa7). At hygroscopic water content, the particles of materials used in the study were composed of 350 and 100 elementary layers for MX80 and FoCa7, respectively.…”
Section: Discussionmentioning
confidence: 99%